Intellectual disability in South Africa: the possibilities and limits of democratic rights. Issue 4 (11th October 2019) - McKenzie, Judith Anne; Abrahams, Toni; Adnams, Colleen; Kleintjes, Sharon
Abstract : Purpose: The purpose of this paper is to present an overview of the history, current status and possible future directions for intellectual disability (ID) policy and practice in South Africa (SA). Design/methodology/approach: The paper was developed by academics and practitioners in the field of ID in SA. A review of the literature, accompanied by a joint writing and discussion process was carried out to identify critical issues in the development of ID services, specifically facing the challenge of moving from racially based provision towards equitable services for all citizens with ID. Findings: Progressive policy has replaced practices of scientific racism which were previously used to support the establishment of white supremacism. This positive move is still in process and has not resulted in the immediate establishment of human rights. A vibrant civil society is engaging with this task currently. Research limitations/implications: The findings point to the need for a human rights approach that takes into account the postcolonial context of SA. Practical implications: There is a need for continued advocacy that is inclusive of people with ID and their families. Social implications: Continuing engagement between government and civil society is recommended to ensure the achievement of human rights for citizens with ID. Originality/value: This paper is of value to ID researchers and practitioners from the global South as it describes a non-western context that might have resonance with other low and middle income countries.